PENGARUH PREOPERATIVE TEACHING TERHADAP PELAKSANAAN MOBILISASI DINI PASIEN PASCA BEDAH APPENDECTOMY - Perama Pradnyani (Coping: Community of Publishing in Nursing, 2014)
Preoperative teaching or preoperative education is defined as supportive measures undertaken by nurses to assist patients improving their own health before and after surgery. Health education may encourage behaviors that support health, prevent disease, treat disease and help the recovery process. One of expected measure is to act postoperative early mobilization. This research is including to the quantitative research model, experimental research type. This research was conducted on May 13 through June 13, 2014 toward appendicitis patients who underwent appendectomy surgery in Sanglah Hospital. The total sample utilized 20 people with the consecutive sampling technique. The test that used to determine the relationship of independent variables and the dependent variable in this study is Mann Whitney U test (p value <?, ? = 0,05). The results of this research indicate that there is a significant association between the administration of preoperative teaching and implementation of early mobilization (p value = 0.008). Based on the results of this research nursing department of Sanglah Hospital is expected to develop and apply the preoperative teaching on patients who will undergo surgery to improve the implementation postoperative early mobilization so that this research can be useful as a preventive action to prevent the occurrence of postoperative complications